Prenatal sonographic diagnosis of VATER association - Tongsong T. (2014)
We examined the potential role of sonography in the prenatal diagnosis of the VATER association, a spectrum of fetal anomalies that includes vertebral defects, imperforate anus, tracheoesophageal fistula, and radial and renal dysplasia.